Angular Phenozaxine Ethers as Potent Multi-microbial Targets Inhibitors: Design, Synthesis, and Molecular Docking Studies - Ezeokonkwo, Mercy A.; Ogbonna, Onyinyechi N.; Okafor, Sunday N.; Godwin-Nwakwasi, Evelyn U.; Ibeanu, Fidelia N.; Okoro, Uchechukwu C. (Frontiers in Chemistry, 2017)
The reaction of diaza-5H-benzo[a]phenoxazin-5-one and 5H-benzo[a]phenoxazin-5-one with various phenols catalyzed by Pd/t-BuXPhos/K3PO4 system gave previously unknown ether derivatives (7a-f and 8a-f) in good yields. UV-visible, FTIR and 1H NMR data were used to confirm structures of the synthesized compounds. The parent compounds and the derivatives were screened in-silico for their drug-likeness and binding affinities to the microbial targets through molecular docking. Molinspiration software and AutoDock were used for the drug-likeness and docking studies respectively.All the synthesized compounds showed strong drug-likeness. They also showed excellent binding affinities with glucosamine-6-phosphate synthase (2VF5), AmpC beta-lactamase (1KE4) and Lanosterol-14α-demethylase (3JUV), with compound 7e having the highest binding energies -9.5, -9.3, and -9.3 kcal/mol respectively. These were found to be higher than the binding energies of the standard drugs. The binding energies of ciprofloxacin with 2VF5 and 1KE4 were -7.8 and -7.5 kcal/mol respectively while that of ketoconazole with 3JUV was -8.6 kcal/mol. The study showed that the synthesized compounds have multi-target inhibitory effects and can be very useful in multi-drug resistance cases. A 2D quantitative structural activity relationship (QSAR) model against target Glucosamine-6-phosphate synthase (2VF5) was developed using partial least squares regression (PLS) with good internal prediction (R2 = 0.7400) and external prediction (R2_ predicted = 0. 5475) via Molecular Operating Environment (2014).